Deep structure and new experimental data of the Bransfield Strait volcanoes (West Antarctica) - V. Soloviev; V. Bakhmutov; N. Yakymchuk; I. Korchagin (Ukrainian Antarctic Journal, 2021)
The aim of the study is to determine the existence of a complex magma-gas-fluid system of the West Antarctica northern volcanic branch in the Bransfield Strait. It consists of several different-level deep magma chambers with magmas raised directly from the mantle or the accumulation zone located at a depth of about 25–30 km. Research methods are based on the known idea that the Earth can be considered a spherical capacitor formed by various layers from its core to the surface with different parameters — thickness, permittivity, density, contact potential difference. Our experimental data show that there is a molten zone at195–225 km where considerable part of volcanic roots is located. Certain structural patterns for land and submarine volcanic structures are revealed, and the first data on the deep migration channels of fluids in the Bransfield Strait are obtained. Volcanic channels are filled with different basic, ultramafic rocks, and sedimentary rocks too. The deep roots of volcanic structures' presence can be associated with the pulsed functioning of a gas-fluid channel with low viscosity. The gas-saturated melts form some zones of intermediate crystallization in the crust due to this channel. These studies showed that multiphase pulsed volcanic activity mainly through the vertical migration channels of deep fluids from the melting zone played a significant role in forming the tectonic diversity and the evolution of the Antarctic continental margin region structures. The results of modified methods of processing and decoding satellite images and photographs allow supplementing the understanding of the West Antarctica structures’ formation. These results of the Bransfield Strait magmatic systems studying indicate the need for further research to understand the mechanism of formation and evolution of structures and deep geospheres in different regions of the Earth.